Cell Therapy for Chemically Induced Ovarian Failure in Mice - Paula Terraciano; Tuane Garcez; Laura Ayres; Isabel Durli; Melchiani Baggio; Cristiana Palma Kuhl; Claudia Laurino; Eduardo Passos; Ana Helena Paz; Elizabeth Cirne-Lima (Stem Cells International)
Cell therapy has been linked to an unexplained return of ovarian function and fertility in some cancer survivors. Studies modeling this in mice have shown that cells transplantation generates donor-derived oocytes in chemotherapy-treated recipients. This study was conducted to further clarify the impact of cell transplantation from different sources on female reproductive function after chemotherapy using a preclinical mouse model. Methods. Female mice were administered 7.5 mg/kg cisplatin followed by cell transplantation (one week later) using GFP+ female cell donors. For cell tracking, adipose derived stem cell GFP+ (ADSC), female germline stem cell GFP+/MVH+ (FGSC), or ovary cell suspension GFP+ mice were transplanted into cisplatin-treated wild-type recipients. After 7 or 14 days animals were killed and histological analysis, IHQ for GFP cells, and ELISA for estradiol were performed. Results. Histological examinations showed that ADSC, ovary cell suspension, and FGSC transplant increase the number of follicles with apparent normal structure in the cells recipient group euthanized on day 7. Cell tracking showed GFP+ samples 7 days after transplant. Conclusion. These data suggest that intraovarian injection of ADSCs and FGSC into mice with chemotherapy-induced ovarian failure diminished the damage caused by cisplatin.